2020
DOI: 10.1080/02713683.2020.1849733
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Sodium Hyaluronate/chondroitin Sulfate Preservative-free Ophthalmic Solution in the Treatment of Dry Eye: A Clinical Trial

Abstract: Purpose: To evaluate the efficacy of a preservative free sodium hyaluronate/chondroitin sulfate ophthalmic solution (SH/CS-PF) in patients with dry eye disease (DED). Methods: This was a randomized phase IV, multicentric, prospective, double-blind clinical trial. Intent-totreat (ITT) and per-protocol (PP) analyses were performed. Patients were assigned to receive either SH/CS-PF, Systane® Ultra (PEG/PG) or Systane® Ultra PF (PEG/PG-PF) for 90 days. A total of 326 patients were included in the ITT, and 217 in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Depending on their application, different systems have been implemented for the administration of chondroitin and its derivatives, including oral administration as food additives, in pharmaceutical preparations, nutraceuticals or veterinary supplements [ 74 , 75 , 76 , 77 ]; incorporation in intra-articular or intravenous injectables [78] ; integration in skin dermatology/cosmeceutical and ophthalmic products [ 79 , 80 , 81 ]; as part of medical devices [ 82 , 83 , 84 , 85 ]; or as biomaterials for regenerative medicine [ 9 , 86 ].…”
Section: Clinical Applications Of Csmentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on their application, different systems have been implemented for the administration of chondroitin and its derivatives, including oral administration as food additives, in pharmaceutical preparations, nutraceuticals or veterinary supplements [ 74 , 75 , 76 , 77 ]; incorporation in intra-articular or intravenous injectables [78] ; integration in skin dermatology/cosmeceutical and ophthalmic products [ 79 , 80 , 81 ]; as part of medical devices [ 82 , 83 , 84 , 85 ]; or as biomaterials for regenerative medicine [ 9 , 86 ].…”
Section: Clinical Applications Of Csmentioning
confidence: 99%
“…In these studies, CS has shown to be safe and, generally, exhibited slight to moderate efficacy over placebo in pain relief and function improvement in osteoarthritis patients. Also, CS is included in eye drop solutions for dry eyes [ 79 , 80 ]. Preservative-free ophthalmic solutions combining xanthan gum and CS or combining sodium HA and CS showed similar efficacy compared to polyethylene glycol and propylene glycol solutions in the treatment of dry eye disease.…”
Section: Clinical Applications Of Csmentioning
confidence: 99%
“…Hyaluronan (HA), heparin (HP), heparan sulfate (HS), and various chondroitin sulfates (CSs) are members of the GAG family that vary in the type of saccharide unit and the geometry of the glycosidic linkage they contain. These glycans are involved in various biological processes through interaction with extracellular signaling molecules (1,2) and have become commonly used drugs (3)(4)(5). Development of chemical tools for imaging, activity-based glycan (or protein) profiling, and pharmacological perturbation of GAGs is urgently needed (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…13 Previous investigations have revealed that CS exerts multiple biological effects and pharmacological activities, such as promoting cell regeneration, 14 anti-inflammation, 15 and antioxidation 16 and has been clinically used for osteoarthritis 17–19 and dry eye treatment. 20,21 The anti-inflammatory property is one of the most important biological activities of CS. 22,23 Our previous study showed that CS ameliorated the prognosis of FK by inhibiting the recruitment of neutrophils and alleviating the inflammatory response by downregulating the TLR-4/nuclear factor-k-gene binding (NF-κB) pathway.…”
Section: Introductionmentioning
confidence: 99%